The Classic Detective Formula in the Novel A Good Girl’s Guide to Murder : A study of John G. Cawelti's formula - Ni Putu Mery Purnami; Ni Ketut Widhiarcani Matradewi; Ni Luh Ketut Mas Indrawati (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to examine how John G. Cawelti's classic detective formula is implemented in Holly Jackson's A Good Girl's Guide to Murder. Using a qualitative descriptive method, this research explores the narrative structure of the novel. The research focuses on how the elements of the formula constructively shape the events that are narrated. Data was collected through reading the novel and note-taking. For the findings, the novel follows the six structural stages outlined in John G. Cawelti (1976) theory: (1) introduction of the detective, (2)crime and clues, (3)investigation, (4)announcement of the solution, (5)explanation of the solution, and (6) denouement. The protagonist of the story is Pippa Fitz-Amobi, a high school student who investigates a long-closed murder case for her school project. The novel adapts classic concepts into a contemporary context through its unique role as a teenage detective. In addition, the conventional detective narrative becomes more innovative by incorporating multimedia formats such as interview transcripts, emails, and diaries. This study found that Jackson's novel successfully blends traditional genre standards with modern storytelling methods, providing a fresh detective experience while maintaining the core structure of classic mystery fiction.